Decoding Peroxidase Gene Function in Heat Stress Adaptation of Tetranychus urticae: Unraveling Molecular Mechanisms of Short-Term Thermal Tolerance - Yaonian Chen; Yuan Liu; Rangjun Wang; Pengcheng Nie; Bin Wei; Rasha S. Abdel-Fattah; Suqin Shang; Youssef Dewer (Antioxidants)
Tetranychus urticae (Acari: Tetranychidae) is a widely distributed agricultural pest, and it possesses an exceptional capacity to withstand or adapt to short-term heat stress. To investigate the molecular mechanisms underlying this heat tolerance, using both transcriptome and whole-genome data, we identified six distinct POD genes in T. urticae and characterized their physicochemical properties and structural features. Real-time quantitative PCR (RT-qPCR) was utilized to analyze the expression profiles of these genes under short-term heat stress. Our results show that T. urticae mitigates heat-induced oxidative stress through the upregulation of POD gene expression, highlighting the critical role of these genes in the mite’s adaptive response to thermal stress. These findings contribute to a deeper understanding of the molecular pathways that enable T. urticae to survive in fluctuating thermal environments, which is increasingly relevant in the context of global climate change. Furthermore, this study provides a foundation for future research utilizing RNA interference (RNAi) technology to further investigate the functional roles of these POD genes and their potential as targets for pest control strategies.